2019
DOI: 10.1111/pai.13066
|View full text |Cite
|
Sign up to set email alerts
|

Parent and child perception of quality of life in a randomized controlled peanut oral immunotherapy trial

Abstract: Background Improved quality of life (QoL) after oral immunotherapy (OIT) in peanut allergic children is often reported by their parents, while the child's perspective is less clear. Objective We aimed to explore whether 2 years of OIT improved QoL in children with peanut allergy and to identify factors influencing change in QoL. Methods In the open‐labeled TAKE‐AWAY peanut OIT trial including children with anaphylaxis to peanuts, 57 were randomized to OIT and 20 to observation. The Pediatric Quality of Life In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 26 publications
0
53
0
1
Order By: Relevance
“…[29][30][31][32][33][34][35] However, data on QOL of children undergoing OIT, from the child perspective, is limited to small or uncontrolled studies. [38][39][40] In the largest group of children studied thus far, we found a significant improvement, both statistically and clinically, in QOL from start to the end of up-dosing of OIT. This improvement was exhibited for all domains, and was not related to the clinical history nor the course of OIT.…”
mentioning
confidence: 64%
“…[29][30][31][32][33][34][35] However, data on QOL of children undergoing OIT, from the child perspective, is limited to small or uncontrolled studies. [38][39][40] In the largest group of children studied thus far, we found a significant improvement, both statistically and clinically, in QOL from start to the end of up-dosing of OIT. This improvement was exhibited for all domains, and was not related to the clinical history nor the course of OIT.…”
mentioning
confidence: 64%
“…In a randomized controlled study performed by Reier-Nilsen et al 34 children and parents were administered the PedsQL 4.0 and FAQL-PB at enrollment, end of up-dosing, and after 2 years. This study reported a significant improvement of the PedsQL scores among children in the OIT group but not in the control group.…”
Section: Introductionmentioning
confidence: 99%
“…No changes on QoL scores in the control group at 18-month follow-up. Reier-Nilsen, 2019 34 Randomized controlled trial (Norway 37 children 5–15 years old Peanut OIT PedsQL 4.0 FAQLQ-PB HRQL scores pre- and post-OIT Yes Significant improvement in children and parents after up-dosing and maintenance phases in both OIT and control groups. The change in QoL was significantly different from the controls for the parental proxy-reports only …”
Section: Introductionmentioning
confidence: 99%
“…In a follow-up study 4 years after treatment was stopped, participants from the PPOIT group were more likely than those from the placebo group to have continued eating peanut (67% vs 4%). Fifty-eight percent of participants from the PPOIT had SU at 8 weeks compared to 17% in the placebo group [19]. These results continue to show the effectiveness in peanut OIT; however, additional studies with these specific therapies (i.e., sealed peanut capsule and adjunctive probiotic use) would need to be replicated in order to assess the role it played in achieving the primary endpoints in comparison to other larger peanut OIT clinical trials.…”
Section: Peanut Oit Clinical Trials Summarymentioning
confidence: 84%